2023
DOI: 10.3390/nano13050788
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Graphene Microsupercapacitors: Structure, Quality, and Performance

Abstract: Laser-induced graphene (LIG) is a graphenic material synthesized from a polymeric substrate through point-by-point laser pyrolysis. It is a fast and cost-effective technique, and it is ideal for flexible electronics and energy storage devices, such as supercapacitors. However, the miniaturization of the thicknesses of the devices, which is important for these applications, has still not been fully explored. Therefore, this work presents an optimized set of laser conditions to fabricate high-quality LIG microsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The D peak is linked to disorders and defects in the graphene structure, while G and 2D peaks are due to carbon atom vibration because of the sp 2 hybridization in the hexagonal lattice and stacking and phonon of the graphene structure, respectively. [26][27][28][29] It could be observed that the D peak intensity in the 100%poly(Ph-dde)-LIG spectrum (Fig. 5(a)) is much more pronounced relative to the D peak intensity in the 50%poly(Ph-dde) : 50%polyimide-LIG spectrum (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The D peak is linked to disorders and defects in the graphene structure, while G and 2D peaks are due to carbon atom vibration because of the sp 2 hybridization in the hexagonal lattice and stacking and phonon of the graphene structure, respectively. [26][27][28][29] It could be observed that the D peak intensity in the 100%poly(Ph-dde)-LIG spectrum (Fig. 5(a)) is much more pronounced relative to the D peak intensity in the 50%poly(Ph-dde) : 50%polyimide-LIG spectrum (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…4(b)).Fig.5(a) and (b) show Raman spectra of the LIG samples the three characteristics peaks, D, G, and 2D at 1350 cm −1 , 1580 cm −1 , and 2680 cm −1 , respectively are shown on the Raman spectra, which conrms the production of graphene on both the substrates. The D peak is linked to disorders and defects in the graphene structure, while G and 2D peaks are due to carbon atom vibration because of the sp 2 hybridization in the hexagonal lattice and stacking and phonon of the graphene structure, respectively [26][27][28][29]. It could be observed that the D peak…”
mentioning
confidence: 99%
“…When comparing the CO 2 laser-irradiated samples, the IR-LrGO-2.0 one, fabricated with the highest power, presents less SSA than the IR-LrGO-1.8 sample. Since the laser beam represents a source of highly concentrated energy, the excess in the power parameter means the structural destruction of the material [42], hence the observed reduction in SSA. When comparing the UV laser-irradiated samples, given a fixed power value, the increase in the exposure time translates into a higher reduction degree and consequently, a higher SSA.…”
Section: Samplementioning
confidence: 99%
“…Laser‐induced carbonization by CO 2 laser has recently caught a lot of attention as an efficient and simple strategy to generate graphene electrodes on carbonizable and flexible substrates in a massive and inexpensive manner, which is highly promising for the fabrication of POC devices [21] . Recent works have successfully fabricated IDEs on polyimide (PI) sheet (or Kapton foil) via laser‐induced carbonization and demonstrated their capability as an electrochemical transducer in energy storage and sensors [22–26] . Nevertheless, to the best of our knowledge, no investigations on the redox cycling ability of the laser‐generated IDEs have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Recent works have successfully fabricated IDEs on polyimide (PI) sheet (or Kapton foil) via laser-induced carbonization and demonstrated their capability as an electrochemical transducer in energy storage and sensors. [22][23][24][25][26] Nevertheless, to the best of our knowledge, no investigations on the redox cycling ability of the laser-generated IDEs have been reported so far. In addition, the inter-electrode distances reported were mostly in the range of a few hundred of micrometers, which may be insufficient to promote redox cycling.…”
Section: Introductionmentioning
confidence: 99%